Bhag-Rembhag Sabhala’an as a Method of Resolving Religious Conflicts in the Madura Legal Tradition - Safi', Safi'; Aidonojie, Paul Atagamen; Jufri, Muwaffiq; Garunja, Evis (El-Mashlahah, 2024)
Religion-based conflicts often occur in various regions, including Madura. However, there is an interesting conflict resolution, namely through the bhag-rembhag sabhala'an tradition. This research aims to determine the mechanism for resolving religious-based conflicts based on local wisdom through bhag-rembhag sabhala'an which is practiced in Madura. This research uses empirical legal research methods with socio-legal and anthropo-legal approaches, which result in the discussion that: First, the resolution of religious conflicts in the context of national law only focuses on efforts to give verdicts of heresy and guilt to parties who, by the religious majority community, are considered contrary to the understanding of the majority of religious believers, not on efforts to open dialogue and find ways of peace between conflicting communities. Second, the resolution of religious conflicts with the bhag-rembhag sabhala'an emphasises efforts to open dialogue between conflicting adherents by utilising local village figures to find a peaceful way and find a variety of similarities amid striking differences caused by the outbreak of religious conflict. Bhag-rembhag Sabhala'an has long been practised in Madura in the event of differences in understanding and religious conflicts, where humanist and peaceful approaches are preferred over violent ways of resolving conflicts. The real contribution of this research is that the mechanism for resolving religious conflicts based on local wisdom can be the primary choice for parties in resolving religious conflicts. This method prioritises peaceful solutions and respect for religious differences.